2014
DOI: 10.1103/physrevlett.113.161601
|View full text |Cite
|
Sign up to set email alerts
|

Solvable Relativistic Hydrogenlike System in Supersymmetric Yang-Mills Theory

Abstract: The classical Kepler problem, as well as its quantum mechanical version, the hydrogen atom, enjoys a well-known hidden symmetry, the conservation of the Laplace-Runge-Lenz vector, which makes these problems superintegrable. Is there a relativistic quantum field theory extension that preserves this symmetry? In this Letter we show that the answer is positive: in the nonrelativistic limit, we identify the dual conformal symmetry of planar N = 4 super Yang-Mills theory with the well-known symmetries of the hydrog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
66
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(71 citation statements)
references
References 37 publications
5
66
0
Order By: Relevance
“…They have found that the split of the degeneracy due to the relativistic correction is milder with more supersymmetry. The result of [4] and ours can be thought of as a confirmation of the continuation of this trend to N = 4 supersymmetry. 1 The rest of the note is organized as follows.…”
Section: Introductionsupporting
confidence: 49%
See 3 more Smart Citations
“…They have found that the split of the degeneracy due to the relativistic correction is milder with more supersymmetry. The result of [4] and ours can be thought of as a confirmation of the continuation of this trend to N = 4 supersymmetry. 1 The rest of the note is organized as follows.…”
Section: Introductionsupporting
confidence: 49%
“…shows an n 2 degeneracy for each principal quantum number n. This can be understood from the existence of an accidental conserved charge [1] which extends the rotational symmetry so(3) to so (4). One way to see this is as follows.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Remarkably, we also observed the appearance of several distinct scales in the QSC which may be thought of as a counterpart to this effective field theory description. In the future it will be also interesting to apply the QSC to study the energies of hydrogen-like bound states in N = 4 SYM [30] which are also related to a φ → π limit. Moreover, our weak coupling results may be useful to establish connections with QCD, similarly to e.g.…”
Section: Jhep12(2016)122mentioning
confidence: 99%